STUDIES ON VARIATIONS IN THE VERTEBRAL COUNTS OF OIL SARDINE ALONG THE NORTH KANARA COAST - Annigeri, G G (Indian Journal of Fisheries, 2011)
The study on the sub-populations of the oil sardine Sardinclla longiceps Val. was made ibased on vertebral counts recorded from specimens collected at seven centres, Karwar, Binage, Shankrubag, Chendia, Bellekeri and Belambar situated over a stretch of about 40 km south along the North Kanara coast and Kankon at a distance of 35 km north of Karwar. In all, 68 samples comprising 2183 specimens in the size range 96-209 mm were examined during the period June 1973 - April 1975. The total number of vertebrae ranged from. 43 to 48, the mode teing at 47. It was found that vertebral variations were not significant in fiih below 160 mm length (mostly juveniles) and those above 160 mm (adults) suggesting that they were homogeneous in character. Data pooled from all centres showed significant difference indicating the possibility that samples drawn were from different sub-populations. Within centres, samples differed significally especially at Binage and Chendia suggesting that these belonged to difl’erent sub-populations. Samples from Karwar, Belambar and Kankon did not differ significantly. It is inferred that sub-populations exist in the oilsardine shoals striking the coast between Karwar, Belambar and Kankon